Effect of Water Hardness on the Offset Printing Quality - (:unkn) unknown (ASIAN JOURNAL OF CHEMISTRY, 2012)
In offset printing, water hardness of the fountain water has an essential influence on the printing process as well as the resulting printed product. Too low and too high water hardness values, trouble-causing carbonates, varying water hardness values and a too high chloride content will disturb the stability. It is known that high calcium monorails will interact with the calcium carbonate in the paper resulting in Milking or Wining of the blankets. Printers, today, should treat their water (soften, purify, etc.) before printing.
Keywords: Offset printing; Water hardness; Fountain solution; Printing quality